Adaptive Fixed-Time Nonsingular Terminal Sliding Mode Attitude Tracking Control for Spacecraft with Actuator Saturations and Faults. (8th February 2021) - Han, Zhiguo; Wang, Minghao; Yan, Xunliang; Qian, Hang
Abstract : This paper focuses on the potential actuator failures of spacecraft in practical engineering applications. Aiming at the shortcomings and deficiencies in the existing attitude fault-tolerant control system design, combined with the current research status of attitude fault-tolerant control technology, we carry out high-precision, fast-convergent attitude tracking algorithms. Based on the adaptive nonsingular terminal sliding mode control theory, we design a kind of fixed-time convergence control method. This method solves the problems of actuator faults, actuator saturation, external disturbances, and inertia uncertainties. The control method includes control law design and controller design. The designed fixed-time adaptive nonsingular terminal sliding mode control law is applicable to the development of fixed-time fault-tolerant attitude tracking controller with multiple constraints. The designed controller considers the saturation of the actuator output torque so that the spacecraft can operate within the saturation magnitude without on-line fault estimation. Lyapunov stability analysis shows that under multiple constraints such as actuator saturation, external disturbances, and inertia uncertainties, the controller has fast convergence and has good fault tolerance to actuator fault. The numerical simulation shows that the controller has good performance and low-energy consumption in attitude tracking control.